2014
DOI: 10.1039/c3dt53637h
|View full text |Cite
|
Sign up to set email alerts
|

A colorimetric “naked-eye” Cu(ii) chemosensor and pH indicator in 100% aqueous solution

Abstract: A new, highly selective and sensitive colorimetric chemosensor 1 for detection of Cu(2+) ions in aqueous solution was developed. Receptor 1 detected Cu(2+) ions by changing its color from colorless to yellow. Moreover, the Cu(2+)-sensitive compound was used as a colorimetric pH detector based on a color change due to 1-Cu(2+) complex formation identifiable by the naked eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…During the last couple of decades, considerable attention has been paid to the design and synthesis of Cu 2+ ion chemosensors, including colorimetric chemosensors [7][8][9][10], fluorescent chemosensors A c c e p t e d M a n u s c r i p t [11][12][13][14] and electrochemical sensors [15][16][17]. Among them, colorimetric chemosensors based on the color changes are more attractive and convenient since they can be monitored by naked eyes directly and avoid using complex instruments.…”
Section: Introductionmentioning
confidence: 99%
“…During the last couple of decades, considerable attention has been paid to the design and synthesis of Cu 2+ ion chemosensors, including colorimetric chemosensors [7][8][9][10], fluorescent chemosensors A c c e p t e d M a n u s c r i p t [11][12][13][14] and electrochemical sensors [15][16][17]. Among them, colorimetric chemosensors based on the color changes are more attractive and convenient since they can be monitored by naked eyes directly and avoid using complex instruments.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion we designed and synthesized a novel DPA-based colorimetric and fluorescent chemosensor 1 that can be utilized as an excellent selective and sensitive colorimetric and fluorescent chemosensor to detect Cu 2+ ion comparing with previously Page 11 of 23 A c c e p t e d M a n u s c r i p t reported probes [31][32][33][34]. Confocal microscopy experiment also showed that the 1 can be used for monitoring Cu 2+ within living HepG2 cells.…”
Section: Discussionmentioning
confidence: 86%
“…These optical sensors were particularly attractive on account of their highly sensitive and selective, quick, inexpensive, easy to fabricate, and non-destructive properties. [4][5][6] However, most chemosensors have been designed and developed to pursue high selectivity to only one metal ion, few of them are "one to more" type. 7-10 Therefore, it is a real challenge to develop a chemosensor for simultaneously detecting and differentiating multi-metal ions.…”
Section: Introductionmentioning
confidence: 99%